Tracing Institutional Role of Technical and Vocational Education and Training Skills for Socio Economic Development of Women in Baluchistan - Aziz Ahmed, Muhammad Shakeel, Aliya Hashmi Khan, (PJE, 2023)
This paper has assessed the tracing institutional role of technical and vocational education and trainings (TVET) for socio-economic development of women in rural and urban areas of Baluchistan. In this descriptive study, a sample of 178 TVET qualified women via three stage stratified sampling technique revealed the role of TVET institutes for socio-economic uplift of women in Baluchistan.